Transformasi Digital Perusahaan Internasional Starbucks Terhadap Peningkatan Daya Saing Perusahaan - Febriani Fajar Wati; Roby Tan; Mashita Ayuni (Serat Acitya, 2022)
This research aimed to analyze the application of digital transformation on international company Starbucks, which is a popular and huge scale coffee company which have more than 20,000 amount of outlets worldwide, towards its competitiveness advantages. The research method used was qualitative research, by gathering data sample from previous researches, articles, journals, and other similar publications in order to justify and to strengthen researcher’s arguments on this topic, especially in context of digital transformation applied by Starbucks to reach their business success. The gathered data be analyzed by qualitative analysis, with the findings resulted that the digital transformations of Starbucks, in which by working toge rease company competitiveness in international market.Digital ther with Postmates, to proceed a delivery app which is integrated with those company due to enable the customers to perform online orders of products in such an easy and practical way are able to inc